Islam Rahmatan Lil 'Alamin - Hannas Hannas; Rinawaty Rinawaty (Theological Journal Kerugma, 2018)
This research found that Islam rah}matan li al-‘a>lami>n in Shamsi Ali’s thought is a grace or welfare for the entire universe, Moslem and non Moslem as well. The concept of Islam rah}matan li al-‘a>lami>n according to Shamsi Ali is implemented in the Muslim’s lifestyle that devoted, peaceful, moderate, dynamic, progressive, democratic, and respectful toward differences which constitutes a blessing and positive contribution to human welfare and dignity. Islam rah}matan li al-‘a>lami>n is described in the gait of da’wah of Shamsi Ali through bi al-Lisa>n da’wah, bi al-Qala>m da’wah, and bi al-H{a>l da’wah by combining various models of da'wah which is also partly known in Christian mission: spiritual growth preaching model, educational preaching model, inclusive preaching model, and open preaching model. The last two models of preachings are unknown in the literature of Christian mission theory and at the same time will be Shamsi Ali’s contribution in the development of da'wah theory. This research promotes some of the previous researches: First, Imam Feisal Abdul Rauf, who stated that the Muslim community in America has applied the Islam rah}matan li al-‘a>lami>n which characterized by building a strong vision to unify moderates, anti-violence and against extremism. Second, Mohamed Al - Hilali explains there is effectiveness of leadership that can be felt by Islam in America. Third, Julie Nava wrote that Muhammad Shamsi Ali is a figure representing Islam rah}matan li al-‘a>lami>n principles. Fourth, Muhammad Fethullah Gülen in Turkey and out side Turkey has proved himself to be an example in applying Islam rah}matan li al-‘a>lami>n. This study refuses or does not support the research of Noor Ul Mobeen which stated that the first generation of Muslim students’ leadership in America in 2009-2012 failed in spelling out Islam rah}matan li al-‘a>lami>n. The approach used in this research: religion, history, leadership, and communication, while the method uses grounded research.